Expressing Generic Reference in Popular Scientific Style - Nohejl, Karel (Univerzita Pardubice, 2014)
The work deals with the use of generic reference in popular scientific text. It describes the use reference in general, the use of individual generic forms and describes their functions. The work focuses on generic use of articles and limiting affect of modification. By contrasting the usage of individual generic forms, it depicts the main differences.
Vyjadřování generické reference v populárně naučném stylu
Keywords: reference; generická reference; atributy; třídy; kategorie; druhy generické reference; omezení generické reference; populárně-vědecký styl; reference; generic reference; attribute; class; category; types of generic reference; limitation of generic reference; popular scientific style